Syntheses, structures and properties of novel oligo(azomethine ether)s containing or not chlorine atoms in the main chain - Kaya, I.; Çulhaoglu, S. (Polimery, 2009)
New oligoazomethines were synthesized via polycondensation of aromatic diamines with one of two dialdehydes. Both dialdehydes, namely 4-({2-[(4-formylphenoxy)methyl]benzyl}oxy)benzaldehyde (2-FPMBB), and 4-({4-[(4-formylphenoxy)methyl]benzyl}oxy)benzaldehyde (4-FPMBB) were prepared from p-hydroxybenzaldehyde with o-xylenedibromide or p-xylenedibromide, respectively. Dialdehydes and oligomers were characterized by FT-IR, 1H NMR and 13C NMR methods. Size exclusion chromatography (SEC) technique was used to determine molecular weights and molecular weight distributions of synthesized oligomers. The thermal stability of oligomers was conducted by thermogravimetric analysis (TGA) and differential thermal analysis (DTA). The weight losses of oligoazomethines (O1, O2, O3 and O4) at 1000° were found to be 54.74, 46.27, 54.85 and 53.10% respectively. In all cases, the imine (-HC=N-) linkage is the first breaking group due to the high temperature. It can be seen from TGA that oligo(azomethine ether)s containing chlorine atoms have higher thermal stability at 1000° than O1 and O3 oligomers.